COL1-Related Disorders: Case Report and Review of Overlapping Syndromes - Gnoli, Maria; Brizola, Evelise; Tremosini, Morena; Pedrini, Elena; Maioli, Margherita; Mosca, Massimiliano; Bassotti, Alessandra; Castronovo, Paola; Giunta, Cecilia; Sangiorgi, Luca (Frontiers in Genetics, 2021)
Collagen type I mutations are related to wide phenotypic expressions frequently causing an overlap of clinical manifestations, in particular between Osteogenesis Imperfecta (OI) and Ehlers-Danlos syndrome (EDS). Both disorders present inter- and intra-familial clinical variability and several clinical signs are present in both diseases. Recently, after the observation that some individuals first ascertained by a suspicion of EDS resulted then carriers of pathogenic variants of genes known to primarily cause OI, some authors proposed the term “COL1-related overlap disorder” to describe these cases. In this paper, we report clinical, molecular and biochemical information about an individual with a diagnosis of EDS with severe joint hypermobility who carries a pathogenic heterozygous variant in COL1A2 gene, and a benign variant in COL1A1 gene. The pathogenic variant, commonly ascribed to OI, as well as the benign variant, has been inherited from the individual’s mother, who presented only mild signs of OI and the diagnosis of OI was confirmed only after molecular testing. In addition, we reviewed the literature of similar cases of overlapping syndromes caused by COL1 gene mutations. The reported case and the literature review suggest that the COL1-related overlap disorders (OI, EDS and overlapping syndromes) represent a continuum of clinical phenotypes related to collagen type I mutations. The spectrum of COL1-related clinical manifestations, the pathophysiology and the underlying molecular mechanisms support the adoption of the updated proposed term “COL1-related overlap disorder” to describe the overlapping syndromes.